Implementasi Konservasi Tanah dan Air berbasis Eco-Habitat di Sekitar Tahura Nipa-Nipa Desa Waworaha Kabupaten Konawe - Indriyani, Lies; Gandri, La; Sudia, La Baco; Kahirun, Kahirun; Siwi, La Ode; Teke, Junartin; Hidayat, Herlan; Lisdayani, Mira; Risnawati, Risnawati; Tiku, Evi Indiriyani (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2024)
Waworaha is one of the village areas in Soropia District, Konawe Regency, where most of the population lives around Tahura Nipa-Nipa and the coastal area. Land use arrangements and soil and water conservation techniques need to be carried out to minimize the impact of climate change, such as flooding, erosion and landslides and ensure the existence of Tahura Nipa-Nipa from anthropogenic damage due to excessive exploitation. The aim of this service is to provide education to the community in efforts to conserve land and water through integrating ecosystems as environmentally friendly and sustainable living spaces. The method used is an educational and participatory approach through socialization activities, distribution and planting of tree seedlings which are carried out jointly. The results of the service implementation that have been carried out are: 1) Identification of problems and coordination with the village government and community; 2) Socialization of the annual role in providing environmental services; 3) Socialization of the role of soil and water conservation in maintaining the sustainability of Taura's environmental services; 4) Providing economically valuable tree seedlings as a medium for soil and water conservation; 5) Joint tree planting action. All of these service activities were welcomed positively by the community of Waworaha Village and took an active role